Revista o cruzeiro: a figura feminina em publicidades de sabonetes de 1949 - Oliveira, Raíssa Medici de; Nascimento, Edna Maria Fernandes dos Santos [UNESP] (My University, 2010)
This article aims at the application of semiotic theory of French line to soap advertisements publicized in the magazine O Cruzeiro in the year 1949. Our objective is to reconstruct the women’s figure present in these texts and to establish its relation to the persuasion of the reader who is led to acquire not only the products, but mainly the values hidden in the announced objects. From the theory we use the generative course of meaning, focusing on the discourse level and assimilating the consumption axiologies proposed by each advertisement. Finally, we intend to assimilate the standard behavior of that society post-Second World War.

O artigo consiste na aplicação da teoria semiótica de linha francesa a publicidades de sabonetes anunciadas na revista O Cruzeiro no ano de 1949. Nosso objetivo é reconstruir a figura feminina presente nesses textos e estabelecer sua relação com a persuasão do enunciatário que é levado a adquirir não somente os produtos, mas principalmente os valores investidos nos objetos anunciados. Da teoria empregamos o percurso gerativo do sentido, focalizando o nível discursivo e depreendendo as axiologias de consumo propostas por cada anúncio publicitário. Finalmente, depreendemos o padrão comportamental daquela sociedade pós-Segunda Guerra Mundial.
Keywords: O Cruzeiro; Women’s figure; Advertisements; 1949; Semiotics; Formas de vida; Mulher; Revista o Cruzeiro